IMPLEMENTASI KEBIJAKAN KREDIT ANGSURAN SISTEM FIDUSIA (KREASI) DI PT. PEGADAIAN CABANG JATIWANGI KABUPATEN MAJALENGKA - Krinawati Krisnawati; Hery Nariyah; Idih Machmud (Universitas Swadaya Gunung Jati, 2013)
This research was conducted and aimed to describe Installment Credit Policy ImplementationFiduciary System (CREATION) at PT. Pawnshop Branch Jatiwangi Majalengka. Thebackground of this research are the author examines terarik Credit Installment FiduciarySystem (CREATION) at PT. Pawnshop Branch Jatiwangi Majalengka. The study wasconducted to determine the extent of Installment Credit Policy Implementation FiduciarySystem (CREATION) at PT. Pawnshop Branch Jatiwangi Majalengka, knowing the factorsthat affect the implementation of the Credit Installment Fiduciary System (CREATION) atPT. Pawnshop Branch Jatiwangi Majalengka also to know the obstacles encountered in theimplementation of Installment Credit Policy Fiduciary System (CREATION) at PT.Pawnshop Branch Jatiwangi Majalengka, and efforts were made to overcome these barriers.The research method used is descriptive qualitative method approach, the study took place atPT. Pawnshop Branch Jatiwangi Majalengka. While the informants in this study is the HeadPT. Pawnshop Branch Jatiwangi Majalengka, executive power paul PT. Pawnshop BranchJatiwangi Majalengka and customer PT. Pawnshop Branch Jatiwangi Majalengka. Datacollection techniques used are literature studies, observation and in-depth interviews. Analysisof data is done through data reduction, data display, and verification and conclusion. Whiletesting the validity of the data dikukan using triangulation techniques. The PolicyImplementation theory used is Edward ІІІ theory, namely: 1. Communication, 2. Sources, 3.Disposition, 4. Bureaucratic structure